OSWALD SCHMIEDEBERG -THE "FATHER" OF EXPERIMENTAL PHARMACOLOGY - Mikhail Pokrovskii; Tatyana Avtina; Elena Zakharova; Yulia Belousova (Belgorod National Research University, 2017)
Biography. Oswald Schmiedeberg (1838-1921) was a son of a bailiff and a maid of honour, the eldest of the six children in the family. He was born and educated in the Russian Empire. Scientific activity. All his life he was completely devoted to science, making experimental pharmacology an independent scientific discipline, and was able to bring it to the international level. O. Schmiedeberg studied the action of muscarine and nicotine, digitoxin, hypnotics and analeptics. He was the first to introduce the concept of "pharmacodynamics" and "pharmacokinetics" of a drug. With his participation, the world's first pharmacological journal was founded, which is still published today. Science school. Working for many years at the University of Strasbourg, Schmiedeberg managed to educate about 120 students - professors from 20 countries of the world, many of whom later founded experimental pharmacology in their countries, for example, Abel in the USA, and N.P. Kravkov in Russia. Scientific activity of Schmiedeberg influenced scholars of his time and for generations to come, creating the preconditions for new high-profile discoveries and even for receiving Nobel prizes. But Oswald Schmiedeberg failed to obtain this high award himself, though he had been nominated 14 times.